Japan’s policy in the South Caucasus (1992-2022) - Harutyunyan, Yeva (History and Culture, 2023)
The region of South Caucasus due to its geographical position and energy carriers possession has a strategic importance, being situated in the center of Eurasia continent and being the most important pivot connecting Asia with Europe. Japan considers the South Caucasus as a part of Central Eurasia and it is greatly interested in establishing peace and stability in the region. Japan’s position towards the conflicts of the South Caucasus is in line with the Western states, in particular, in the issue of the resolution of Nagorno Karabakh conflict, it gives priority to the OSCE Minsk Group’s activities and supports the early peaceful settlement of the conflict, while in the issues of Abkhazia and South Ossetia, Japan supports the preservation of the territorial integrity of Georgia. In the article the development trends of Japan’s foreign policy in the South Caucasus as a part of Central Eurasia continent were presented in four stages of development: • The phase of familiarization and establishment of diplomatic relations (1991-1996), • "Eurasian" or "Japanese Silk Road" conceptual policy (1997-2003), • Conceptual policy of "Central Asia plus Japan" dialogue (2004-2018), • "Japan’s Caucasus Initiative" policy (from 2018 till now). Japan implements its economic policy towards the South Caucasus states through the ODA program, providing bilateral and multilateral aid for developing the target sectors in three republics of the region.